Wind speed and direction measurement based on arc ultrasonic sensor array signal processing algorithm. (November 2016) - Li, Xinbo; Sun, Haixin; Gao, Wei; Shi, Yaowu; Liu, Guojun; Wu, Yue
Abstract: This article investigates a kind of method to measure the wind speed and the wind direction, which is based on arc ultrasonic sensor array and combined with array signal processing algorithm. In the proposed method, a new arc ultrasonic array structure is introduced and the array manifold is derived firstly. On this basis, the measurement of the wind speed and the wind direction is analyzed and discussed by means of the basic idea of the classic MUSIC (Multiple Signal Classification) algorithm, which achieves the measurements of the 360° wind direction with resolution of 1° and 0–60 m/s wind speed with resolution of 0.1 m/s. The implementation of the proposed method is elaborated through the theoretical derivation and corresponding discussion. Besides, the simulation experiments are presented to show the feasibility of the proposed method. The theoretical analysis and simulation results indicate that the proposed method has superiority on anti-noise performance and improves the wind measurement accuracy. Highlights: An arc ultrasonic sensor array signal processing algorithm is proposed for the wind speed and direction measurement. The measurement is transformed into the parameter identification problem of sensor array output vector. The proposed method can be applied to whole angle wind direction measurement. The proposed algorithm does not have ambiguity problems.